EFFECTS OF ENVIRONMENTAL MANAGEMENT SYSTEMS ON ENVIRONMENTAL MANAGEMENT PRACTICES AND OPERATIONS - SROUFE, ROBERT (Production and Operations Management, 2003)
To date, it is unclear as to how Environmental Management Systems (EMS) are implemented and what effects these systems have on other environmental and operational practices. This study reports empirical insights to EMS practices based on the largest EMS survey of manufacturing firms in the United States. The objective of the study is to test for a relationship between environmental management systems and perceived operations performance while considering direct and indirect effects of various environmental practices. The results of this study are supported by several field studies and provide a new source of information regarding EMS theory development. The results also indicate a positive relationship between an EMS, the environmental practices a firm engages, and operations performance measures.